2020
DOI: 10.3390/antiox9100958
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants as an Epidermal Stem Cell Activator

Abstract: Antioxidants may modulate the microenvironment of epidermal stem cells by reducing the production of reactive oxygen species or by regulating the expression of extracellular matrix protein. The extracellular membrane is an important component of the stem cell niche, and microRNAs regulate extracellular membrane-mediated basal keratinocyte proliferation. In this narrative review, we will discuss several antioxidants such as ascorbic acid, plant extracts, peptides and hyaluronic acid, and their effect on the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 145 publications
(190 reference statements)
1
2
0
Order By: Relevance
“…The addition of RSV, CoQ10, or in combination with the hMSCs improved the number of cells during the growth curve, increased cell viability, and decreased levels of LDH. These effects are supported by what was previously described regarding the antioxidants effects of molecules by reducing oxidative stress and ROS ( Zeng et al, 2015 ; Kwon and Park, 2020 ), thereby improving cell proliferative (activating ERK1/2 and p38 MAPK), survival, and differentiation capacity when supplemented in cell cultures ( Dai et al, 2007 ; Shaban et al, 2017 ; Shafi et al, 2019 ).…”
Section: Discussionsupporting
confidence: 80%
“…The addition of RSV, CoQ10, or in combination with the hMSCs improved the number of cells during the growth curve, increased cell viability, and decreased levels of LDH. These effects are supported by what was previously described regarding the antioxidants effects of molecules by reducing oxidative stress and ROS ( Zeng et al, 2015 ; Kwon and Park, 2020 ), thereby improving cell proliferative (activating ERK1/2 and p38 MAPK), survival, and differentiation capacity when supplemented in cell cultures ( Dai et al, 2007 ; Shaban et al, 2017 ; Shafi et al, 2019 ).…”
Section: Discussionsupporting
confidence: 80%
“…Miller et al found that superoxide and H 2 O 2 levels were significantly increased near calcified regions in explanted valves from patients with established aortic stenosis [ 40 ]. This is likely one of the reasons for AA’s anti-calcification effects, since it acts as an electron donor to reduce the production of ROS and, therefore, helps prevent DNA damage, oxidation of amino acid residues, as well as lipid peroxidation [ 41 ]. These findings support our selection of antioxidants to test, as they were shown to have protective effects against oxidative stress-induced through H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that HA has double functionality as anticoagulant and promoter of endothelialization [85]. Several reports have demonstrated the antioxidant properties of HA [86], exerted by ROS scavenging activity thus protecting cells from oxidative stress-induced damages [87]. In a rat model of carbon tetrachloride-induced liver injury, injection of HA reduced serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) rise and lipid peroxidation, and increased superoxide dismutase (SOD) and glutathione peroxidase activities [88].…”
Section: Hyaluronic Acidmentioning
confidence: 99%